Educational Environment and a Smart City - T. F. Starovoitova; V. K. Shesholko; I. A. Starovoitov (Цифровая трансформация, 2024)
In the modern world, the integration of digital technologies into various spheres of life stimulates the development of the concept of smart cities, where digital innovations are used to optimize the management of resources, infrastructure and education. The article discusses the importance of digital education in the context of a smart city, emphasizing its role in the formation of the educational environment and the development of society. A study conducted in Minsk among students, graduates and retraining students reveals the requirements for digitalization of education and its impact on educational processes in a smart city. The survey results provide valuable data for the development and implementation of a unified urban educational environment based on digital platforms.